The Effect of Competence and Compensation on Employee Performance at the Tangerang Area Swamitra Savings and Loan Unit - Alidin Alidin; Muhammad Ridwan (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
This study aims to examine and analyze the influence of competency and compensation on employee performance at the Swamitra Credit Union Unit in the Tangerang area. This quantitative research uses primary data obtained from questionnaires distributed to employees of the Swamitra Credit Union Unit in the Tangerang area. The sampling technique used is saturated sampling, meaning all members of the population are used as samples, totaling 80 respondents. The data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, determination tests, and path analysis using SPSS (Statistical Package for the Social Sciences). The partial test results show that competency has a significant effect on employee performance with a t-value of 3.441 (3.441 > 1.991) and a significance value of 0.001 (0.001 < 0.05). Compensation also significantly affects employee performance with a t-value of 4.473 (4.473 > 1.991) and a significance value of 0.000 (0.000 < 0.05). Simultaneously, competency and compensation significantly influence employee performance with an F-value of 30.803 (30.803 > 3.11) and a significance value of 0.000 (0.000 < 0.05). This study is expected to provide additional references regarding competency, compensation, and employee performance